CE-UV/VIS and CE-MS for monitoring organic impurities during the downstream processing of fermentative-produced lactic acid from second-generation renewable feedstocks. Issue 1 (December 2016) - Laube, Hendrik; Matysik, Frank-Michael; Schmidberger, Andreas; Mehlmann, Kerstin; Toursel, Andreas; Boden, Jana
Abstract Background During the downstream process of bio-based bulk chemicals, organic impurities, mostly residues from the fermentation process, must be separated to obtain a pure and ready-to-market chemical. In this study, capillary electrophoresis was investigated for the non-targeting downstream process monitoring of organic impurities and simultaneous quantitative detection of lactic acid during the purification process of fermentatively produced lactic acid. The downstream process incorporated 11 separation units, ranging from filtration, adsorption and ion exchange to electrodialysis and distillation, and 15 different second-generation renewable feedstocks were processed into lactic acid. The identification of organic impurities was established through spiking and the utilization of an advanced capillary electrophoresis mass spectrometry system. Results A total of 53 % of the organic impurities were efficiently removed via bipolar electrodialysis; however, one impurity, pyroglutamic acid, was recalcitrant to separation. It was demonstrated that the presence of pyroglutamic acid disrupts the polymerization of lactic acid into poly lactic acid. Pyroglutamic acid was present in all lactic acid solutions, independent of the type of renewable resource or the bacterium applied. Pyroglutamic acid, also known as 5-oxoproline, is a metabolite in the glutathione cycle, which is present in all living microorganisms. pyroglutamic acid is found in many proteins, and during intracellular protein metabolism, N-terminal glutamic acid and glutamine residues can spontaneously cyclize to become pyroglutamic acid. Hence, the concentration of pyroglutamic acid in the lactic acid solution can only be limited to a certain amount. Conclusions The present study proved the capillary electrophoresis system to be an important tool for downstream process monitoring. The high product concentration encountered in biological production processes did not hinder the capillary electrophoresis from separating and detecting organic impurities, even at minor concentrations. The coupling of the capillary electrophoresis with a mass spectrometry system allowed for the straightforward identification of the remaining critical impurity, pyroglutamic acid. Although 11 separation units were applied during the downstream process, the pyroglutamic acid concentration remained at 12, 900 ppm, which was comparatively high. All organic impurities found were tracked by the capillary electrophoresis, allowing for further separation optimization.